2020
DOI: 10.1021/acsnano.0c03962
|View full text |Cite
|
Sign up to set email alerts
|

Local Environment Affects the Activity of Enzymes on a 3D Molecular Scaffold

Abstract: The ability to coordinate and confine enzymes presents an opportunity to affect their performance and to create chemically active materials. Recent studies show that polymers and biopolymers can be used to scaffold enzymes, and that can lead to the modulated biocatalytic efficiency. Here, we investigated the role of microenvironments on enzyme activity using a well-defined molecular scaffold. An enzyme, glucose oxidase (GOx), was positioned at different locations of a three-dimensional (3D) octahedral DNA scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…DNA nanotechnology offers an immense capability for fabrication complexity in designed scaffolds, 9 , 24 , 25 but due to the contribution of different effects it is difficult to distill the leading causes of activity changes of enzymatic cascades scaffolded on such systems. Specifically, DNA scaffold effects can induce changes in local proton concentration, consequently affecting local pH, 18 , 26 , 27 as well as potential substrate channeling either by direct proximity 12 , 27 30 or intermediate exchange through a scaffold hydration layer. 5 , 15 , 16 , 27 , 31 These topics have been a source of discussion in recent years, particularly regarding the contributing factors behind increased colocalized enzyme activity on DNA scaffolds, 5 , 27 , 32 36 such as impacts on substrate diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…DNA nanotechnology offers an immense capability for fabrication complexity in designed scaffolds, 9 , 24 , 25 but due to the contribution of different effects it is difficult to distill the leading causes of activity changes of enzymatic cascades scaffolded on such systems. Specifically, DNA scaffold effects can induce changes in local proton concentration, consequently affecting local pH, 18 , 26 , 27 as well as potential substrate channeling either by direct proximity 12 , 27 30 or intermediate exchange through a scaffold hydration layer. 5 , 15 , 16 , 27 , 31 These topics have been a source of discussion in recent years, particularly regarding the contributing factors behind increased colocalized enzyme activity on DNA scaffolds, 5 , 27 , 32 36 such as impacts on substrate diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…[ 111 ] The recent detailed studies revealed that DNA origami can affect local pH environments of enzyme which affect its activity. [ 146 ]…”
Section: Self‐assembled Dna Nanostructuresmentioning
confidence: 99%
“…Gang and co‐workers employed a 3D DNA origami scaffold of octahedral shape to place a glucose oxidase (GOx), which was prescribed to either externally at one of the vertices or internally, along one of the duplex bundles ( Figure A). [ 28 ] The two positions had different densities of the negative charges, as defined by the amount of DNA spatially surrounding the enzyme. They demonstrated that the GOx conjugated on vertices had 30% higher catalytic activity than that on the duplex bundle, which had less local polyanions and more acidity.…”
Section: Local Ph Effectmentioning
confidence: 99%
“…The oxidation efficiency of glucose was affected by the density of negative charge at different positions of the scaffold. [ 28 ] Reproduced with permission. [ 28 ] Copyright 2020, American Chemical Society.…”
Section: Local Ph Effectmentioning
confidence: 99%
See 1 more Smart Citation